The Effectiveness of Outdoor Education on Student Creativity - Yogi Akin; Ryan Abu Bakar (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effect of outdoor education activities on student creativity. The method used in this study is an experimental method with a static group comparison design. The sample in this study were PGSD Physical Education students using a purposive sampling technique, totalling 40 students, namely 20 students who did outdoor education activities and 20 students who did not do outdoor education activities. The research instrument was a creativity questionnaire which was analyzed with the statistical technique of the Two-Average Equivalence Test with the treatment of outdoor education activities given six days in 2 weeks. Based on the data analysis, the hypothesis is accepted, which means that outdoor education activities have a significant effect on student creativity. This study concludes that outdoor education activities have a significant positive impact on student creativity. Outdoor education activities can be a good alternative in learning to increase creativity and other cognitive components.